Knowledge exchange: Proceedings of the policy roundtable on ATMI-ASEAN: The case of the maize industry in Cambodia - Southeast Asian Regional Center for Graduate Study and Research in Agriculture; International Food Policy Research Institute (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2020)
The Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA) and the International Food Policy Research Institute (IFPRI), in partnership with the Ministry of Agriculture, Forestry and Fisheries (MAFF), organized the policy roundtable (PRT) on the case of maize industry in Cambodia under the project Agricultural Transformation and Market Integration in the ASEAN Region: Responding to Food Security and Inclusiveness Concerns (ATMI-ASEAN) on 11 December 2018. Funded by the International Fund for Agricultural Development (IFAD) and implemented by IFPRI (lead) and by SEARCA (implementing partner), ATMI-ASEAN focused on strengthening the institutional capacities of ASEAN Member States (AMS) to develop and implement policies and subregional programs in support of the integration of smallholders in agriculture and food markets. Specifically, the targeted AMS were Cambodia, Myanmar, Lao PDR, Vietnam, and the Philippines. The PRT was the first major event of the ATMI-ASEAN project in Cambodia concerning maize or corn, Cambodia’s third-largest agricultural commodity produced, next to rice and cassava.